How do generic cognitive strategies affect proceeding in freshmen's engineering design? Results of a pilot study in engineering design education. (2nd February 2015) - Melzer, Marlen; Hacker, Winfried
The innovative impact of technical products strongly depends on the ways of proceeding in the early phases of engineering design. Within a quasi–experimental randomised control group design including 95 engineering design students forming 21 groups, we analysed whether offering a system of generic cognitive strategies in addition to the regular curriculum in engineering design methodology may significantly improve engineering students' knowledge, ways of proceeding, and performance. The additionally provided strategies are associated with a significantly larger increase of reported knowledge on generic cognitive techniques and strategies utilised by a greater proportion of teams assigned to the experimental group. These results suggest integrating generic cognitive strategies into the regular engineering design curriculum.